Aspects of Multilingualism in Chimamanda Ngozi Adichie’s Purple Hibiscus - Fazakas, Edit (Acta Universitatis Sapientiae, Philologica, 2024)
When examining the topic of multilingualism, Nigeria emerges as a captivating subject due to its renowned linguistic diversity. Authors who have a bicultural background encompassing African and European language cultures consistently exhibited a type of hybridity in their use of the colonial language. Consequently, a unique European linguistic variation emerged as a result of this. Chimamanda Ngozi Adichie demonstrates a strong inclination to transcend the extensive language debates prevalent in the history of African literature. What is more, she asserts her use of English and her interjections in Igbo as normative rather than confrontational. Adichie frequently incorporates Igbo vocabulary, phrases, and proverbial expressions into her predominantly English writing, demonstrating a profound understanding of the enduring influence of English colonialism. However, Adichie also embraces and skilfully uses English as a universal language, transcending its postcolonial connotations. Consequently, she possesses the ability to access and engage with a broader spectrum of global literary traditions and contemporary movements. The primary focus of this study has been the elucidation of the manifestation of multilingualism in the fiction of the Nigerian writer, Chimamanda Ngozi Adichie. The motivational elements of code-switching, which Adichie uses to express various aspects of oppression and cultural hybridity, have received a great deal of attention.